Research into stope roof control of compound roof by solid backfilling mining - Gao, R.; Zhang, J.; Spearing, Sam; Li, M.; An, B.; Hao, D. (Elsevier, 2015)
Based on the analysis of the failure characteristics and backfilling effect of the compound roof at 1801 backfilling workface in Taiyuan coal mine, China, we propose a method of controlling the pre-subsidence of a compound roof by using pre-stressed bolts to improve the backfilling ratio of the workface so as to maintain the global stability of the stope roof. In addition, PHASE simulation software was employed to analyze the influence law of pre-stressing force, length, and interval on roof subsidence at the workface. On the basis of the numerical simulation results, a model for calculating the pre-stressing force and length of the bolts, the interval between the bolts, as well as roof subsidence at the workface, was established by using SPSS regression analysis software. Moreover, the research results were applied successfully to the 1801 filling workface. According to the monitoring data of roof closure, it was found that the final subsidence value for the goaf roof was 350 mm and the filling ratio at the workface was 86%, which could fully meet the demand for safety production at the workface. The safe and effective control of the stope roof was therefore realized, which achieves the goal of safe and efficient backfilling mining under a compound roof.